Determination of Phenylalanine Metabolites in Rat Tissues by Gas-Liquid Chromatography (Revista Española de Fisiología, 1976)
A rapid and accurate gas-liquid chromatographic method for the quantitative determination of phenylalanine metabolites is described. All the steps for their extraction from blood, liver and brain of the rat and their conversion into volatile derivatives are detailed. The following acids have been determinad: benzoic, phenylacetic, mandelic, o-hydroxyphenylacetic, phenyllactic, p-hydroxyphenylacetic and phenylpyruvic.